Cavity nesting ants use more, larger grains of sand for nest entrance modification in repeated emigrations - M. Marczak; A. Gruszka; M. Rolski; S. Mitrus (The European Zoological Journal)
Nest sites are important for social insects, as the nests provide refuge against enemies and ensure optimal conditions for brood development. It was previously shown that ant colonies can consistently vary in terms of the structure of specific parts of the nest, such as the nest walls. In this study, we ask whether colonies differ in using material for nest entrance modification in repeated emigrations. Colonies of the cavity-nesting ant Temnothorax crassispinus were kept in artificial nest sites. After an acclimatisation period, dry sand was added in an arena. Grains of sand were collected to be used for the modification of the nest site. Then, the colonies were forced to change their nest site, and the procedure was repeated. For the nest entrance modification, colonies used different numbers of grains of sand. We found a positive correlation between the number of grains used during the first and the second trials by specific colonies. Additionally, during the second trial the colonies used more grains of sand, and proportionally more of the larger grains. These results suggest that ants are able to quickly adjust specific behaviour to a situation, i.e. they are able to select specific size of grains of sand.